W-representations of the fermionic matrix and Aristotelian tensor models - Lu-Yao Wang (Elsevier, 2021)
We show that the fermionic matrix model can be realized by W-representation. We construct the Virasoro constraints with higher algebraic structures, where the constraint operators obey the Witt algebra and null 3-algebra. The remarkable feature is that the character expansion of the partition function can be easily derived from such Virasoro constraints. It is a τ-function of the KP hierarchy. We construct the fermionic Aristotelian tensor model and give its W-representation. Moreover, we analyze the fermionic red tensor model and present the W-representation and character expansion of the partition function.